Effects of magnetic saturation on induction machines driven by static converters - Andrade,Darizon A. de (2004)
The effects of magnetic saturation on the operation of induction motors driven by static converters are analyzed. A mathematical model based on magnetic harmonic functions is used to account for saturation. Distortions on the air gap flux due to non-linear magnetic characteristics lead to appearance of space harmonics in the resultant flux density distribution. This causes specific distortions in stator and rotor time quantities, which are different from those due to static converter. Operation with six pulse and sinusoidal PWM converters under saturated conditions is considered. Comparisons of experimental and simulated results are presented and found to be in very good agreement.